First-principles study of CO and OH adsorption on in-doped ZnO surfaces. (September 2019) - Saniz, R.; Sarmadian, N.; Partoens, B.; Batuk, M.; Hadermann, J.; Marikutsa, A.; Rumyantseva, M.; Gaskov, A.; Lamoen, D.
Abstract: We present a first-principles computational study of CO and OH adsorption on non-polar ZnO (10 1 ¯ 0) surfaces doped with indium. The calculations were performed using a model ZnO slab. The position of the In dopants was varied from deep bulk-like layers to the surface layers. It was established that the preferential location of the In atoms is at the surface by examining the dependence of the defect formation energy as well as the surface energy on In location. The adsorption sites on the surface of ZnO and the energy of adsorption of CO molecules and OH-species were determined in connection to In doping. It was found that OH has higher bonding energy to the surface than CO. The presence of In atoms at the surface of ZnO is favorable for CO adsorption, resulting in an elongation of the C-O bond and in charge transfer to the surface. The effect of CO and OH adsorption on the electronic and conduction properties of surfaces was assessed. We conclude that In-doped ZnO surfaces should present a higher electronic response upon adsorption of CO.